The Structure and Measurement of Labor Value in China Based on a Sample of Children Aged 8–12 Years - Chao, Xiaomei; Wang, Weihua (Frontiers in Psychology, 2020)
The core of labor education is to shape labor values. For China, a socialist country, the purpose of labor education is to establish labor values based on the sinicization of Marxism. Thus, according to the theoretical analysis of labor values and the interpretation of government policies of Chinese scholars, the present study constructed a scale on labor values from five dimensions: honest labor value, equality status of labor value, cherishing labor value, loving labor value and distribution value according to work. By using exploratory factor analysis and confirmatory factor analysis, this scale was able to achieve high reliability and validity, as well as high external correlation validity. Notably, this was the first study to develop a scale on labor values from the perspective of empirical research, promoting an empirical trend in labor value research.